Werte in einer olympischen Pädagogik - Kovar, P. (Leipziger Sportwissenschaftliche Beiträge, 2016)
Originally, the Olympic idea of Pierre de Coubertin was an educational one. Five basic values of the Olympism have been transferred in newer didactic concepts by Lenk, Grupe, and Müller. The article gives a short overview and describes the topics of those values, which belong to an Olympic Education or Olympic Pedagogy. Furthermore, in which way young people develop such values of Olympism and which educational implications are conceivable for a successful value mediation in the Olympic Pedagogy.